On Both Sides of the Strait of Gibraltar : Studies in the history of medieval astronomy in the Iberian Peninsula and the Maghrib - Samsó, Julio, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2020)
"In On Both Sides of the Strait of Gibraltar Julio Samsó studies the history of medieval astronomy in al-Andalus (Muslim Spain), the Maghrib and the Christian kingdoms of the Iberian Peninsula. He proves that the Arabic, Latin, Hebrew, Castilian and Catalan sources belong to the same tradition whose origin can be dated in the 11th century due to the changes in Ptolemy's astronomical theory introduced by the Toledan astronomer Ibn al-Zarqālluh/Azarquiel. The book also analyses the role of al-Andalus and the Iberian Peninsula in the transmission of Islamic astronomy to Europe and justifies the fact that Eastern Islamic works published after ca. 950 CE were not accessible to medieval European scholars because they had not reached al-Andalus"--